2022
DOI: 10.48550/arxiv.2202.04805
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Understanding Hyperdimensional Computing for Parallel Single-Pass Learning

Abstract: Hyperdimensional computing (HDC) is an emerging learning paradigm that computes with high dimensional binary vectors. It is attractive because of its energy efficiency and low latency, especially on emerging hardware-but HDC suffers from low model accuracy, with little theoretical understanding of what limits its performance. We propose a new theoretical analysis of the limits of HDC via a consideration of what similarity matrices can be "expressed" by binary vectors, and we show how the limits of HDC can be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In general, an HDC classifier can use record-based or 𝑁 -gram-based encoders [3]. While our training approach applies to any encoding methods (including advanced ones [20] based on sophisticated feature extractions), 2 for a concrete case study, we adopt the commonly-used record-based encoding which, shown in Eq. 1, has higher accuracy than the 𝑁gram-based method for many applications [3].…”
Section: Binary Hdcmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, an HDC classifier can use record-based or 𝑁 -gram-based encoders [3]. While our training approach applies to any encoding methods (including advanced ones [20] based on sophisticated feature extractions), 2 for a concrete case study, we adopt the commonly-used record-based encoding which, shown in Eq. 1, has higher accuracy than the 𝑁gram-based method for many applications [3].…”
Section: Binary Hdcmentioning
confidence: 99%
“…Per the DAC'22 policy, we are not allowed to make significant non-editorial changes to papers once accepted. Thus, as Ref [20]. (arXiv date 2/10/2022) was not available or cited at the time of our DAC'22 submission on 11/22/2021, it will not be included in the final camera-ready version of this paper.…”
mentioning
confidence: 99%